Total Quality Management System and Organisation Performance: Mediating Effect of Organisational Learning in Nepali Service Sector - Saud, Tina Rawal (Journal of Business and Social Sciences Research, 2019)
The main objective of this study was to examine the effect of total quality management system (TQM) on organisation performance along with the mediating effect of organisation learning in Nepali Service sector. The relationship between the TQM system, organisation learning and organisation performance was examined using Pearson correlation coefficient and regression analysis was conducted to test the hypotheses. Data was collected from 240 respondents (i.e., 118 from the ISO certified and 122 from non-ISO certified organisations). The findings of this study suggested that total quality management system had a significant positive effect on organisation performance and organisation learning mediated the relationship between total quality management system and organisation performance. Out of the seven dimensions of the TQM system only top management support, workforce management, customer relations, supplier quality management and process flow management had a significant positive effect on organisation performance. The results of the independent sample t-test further confirmed the high level of organisation performance in ISO certified organisations.